Konflik Sosial Dalam Novel Senja di Jakarta Karya Mochtar Lubis - Nufus, Adlina Amanda; Warsiman, Warsiman; Rohman, Muh. Fatoni (Aksara: Jurnal Bahasa dan Sastra, 2025)
The novel "Senja in Jakarta" depicts the political, social and economic life of Indonesian society in the era of Liberal Democracy and Guided Democracy, especially in Jakarta during the 1950s. This novel depicts the dirty political practices of manipulators, fraudsters and corrupt officials in Jakarta against the background of the lives of ordinary people. This research aims to describe the social conflicts contained in the novel, namely realistic and non-realistic conflicts as well as the positive function of these social conflicts. Realistic conflict arises from dissatisfaction or disappointment experienced by individuals or groups with a system or demands in social relations. On the other hand, non-realistic conflicts are driven by irrational and ideological desires. This research uses a qualitative descriptive method with a literary sociology approach. The data used in this research are text excerpts in the form of dialogues, monologues and narratives that describe social conflicts in the novel "Senja in Jakarta". The data collection instruments used were documentation and observation using reading and note-taking techniques. The data analysis process includes repeated reading, highlighting, documentation, and data analysis using Lewis A. Coser's social conflict theory. Then, four realistic social conflict data were found, consisting of two data related to hostile feelings, and two data related to hostile behaviour, two data on unrealistic social conflict, and two data on the positive function of social conflict. This research connects the depiction of social conflict in the novel "Senja in Jakarta" with the reality of Indonesian society in the 1950s, thereby showing that conflict, both realistic and non-realistic, will give rise to functions that shape the social structure and identity of Indonesian society in the 1950s.Keywords: Novel Twilight in Jakarta, Sociology of Literature, Social Conflict